Sustainable Values in the Structure of Traditional Osing Houses in Indonesia - Cindy Puspita; Agus Dwi Hariyanto; Lilianny S. Arifin (Architecture, 2025)
The worldwide energy crisis is causing people in most countries to reduce their energy use to prevent the next generation from being unable to fulfill their needs. The Osing people use sustainability values based on traditions passed down from generation to generation with appropriate technology to fit the needs of the people and their environment. This research employs a qualitative descriptive method with a literature review and data collection. Based on the framework used by Iwanmura, Osing house construction primarily focuses on the principles of low impact and health and amenity. This study reveals that the architectural design and construction process of an energy-efficient traditional building can be adapted to contemporary sustainable housing. The primary aim was to identify and analyze sustainability values in the construction process and techniques of traditional Osing houses in Kemiren Village, Banyuwangi, which can serve as a reference for modern sustainable architecture practices. The study reveals the uniqueness of traditional Osing construction using the local material Bendo wood, which can be dismantled from the foundation up to the roof joint systems, thus allowing the materials to be repaired and recycled down to the smallest parts and minimizing construction waste. The advantage of this building construction process is the use of traditional housing techniques to minimize the need for mechanical systems. This traditional construction method, using wood as the building material and considering climatic features, demonstrates how to achieve sustainable building values throughout all elements of a building that provides users with comfort and safety.